Pandemic depression: COVID-19 and the mental health of the self-employed - Marco Caliendo; Daniel Graeber; Alexander Kritikos; Johannes Seebauer (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
We investigate the effect of the COVID-19 pandemic on self-employed people's mental health. Using representative longitudinal survey data from Germany, we reveal differential effects by gender: whereas self-employed women experienced a substantial deterioration in their mental health, self-employed men displayed no significant changes up to early 2021. Financial losses are important in explaining these differences. In addition, we find larger mental health responses among self-employed women who were directly affected by government-imposed restrictions and bore an increased childcare burden due to school and daycare closures. We also find that self-employed individuals who are more resilient coped better with the crisis.
Keywords: L26; D31; I14; I18; J16; 330; self-employment; COVID-19; mental health; gender; representative longitudinal survey data; PHQ-4 score; resilience